Cross-subunit catalysis and a new phenomenon of recessive resurrection in Escherichia coli RNase E. Issue 2 (5th December 2019) - Ali, Nida; Gowrishankar, Jayaraman
Abstract: RNase E is a 472-kDa homo-tetrameric essential endoribonuclease involved in RNA processing and turnover in Escherichia coli . In its N-terminal half (NTH) is the catalytic active site, as also a substrate 5′-sensor pocket that renders enzyme activity maximal on 5′-monophosphorylated RNAs. The protein's non-catalytic C-terminal half (CTH) harbours RNA-binding motifs and serves as scaffold for a multiprotein degradosome complex, but is dispensable for viability. Here, we provide evidence that a full-length hetero-tetramer, composed of a mixture of wild-type and (recessive lethal) active-site mutant subunits, exhibits identical activity in vivo as the wild-type homo-tetramer itself ('recessive resurrection'). When all of the cognate polypeptides lacked the CTH, the active-site mutant subunits were dominant negative. A pair of C-terminally truncated polypeptides, which were individually inactive because of additional mutations in their active site and 5′-sensor pocket respectively, exhibited catalytic function in combination, both in vivo and in vitro (i.e. intragenic or allelic complementation). Our results indicate that adjacent subunits within an oligomer are separately responsible for 5′-sensing and cleavage, and that RNA binding facilitates oligomerization. We propose also that the CTH mediates a rate-determining initial step for enzyme function, which is likely the binding and channelling of substrate for NTH's endonucleolytic action.